Prolactin Variants in Human Pituitaries and Pituitary Adenomas Identified With Two-Dimensional Gel Electrophoresis and Mass Spectrometry - Qian, Shehua; Yang, Yongmei; Li, Na; Cheng, Tingting; Wang, Xiaowei; Liu, Jianping; Li, Xuejun; Desiderio, Dominic M.; Zhan, Xianquan (Frontiers in Endocrinology, 2018)
Human prolactin (hPRL) plays multiple roles in growth, metabolism, development, reproduction, and immunoregulation, which is an important protein synthesized in a pituitary. Two-dimensional gel electrophoresis (2DE) is an effective method in identity of protein variants for in-depth insight into functions of that protein. 2DE, 2DE-based PRL-immunoblot, mass spectrometry, and bioinformatics were used to analyze hPRL variants in human normal (control; n = 8) pituitaries and in five subtypes of pituitary adenomas [NF- (n = 3)-, FSH+ (n = 3)-, LH+ (n = 3)-, FSH+/LH+ (n = 3)-, and PRL+ (n = 3)-adenomas]. Six hPRL variants were identified with different isoelectric point (pI)-relative molecular mass (Mr) distribution on a 2DE pattern, including variants V1 (pI 6.1; 26.0 kDa), V2 (pI 6.3; 26.4 kDa), V3 (pI 6.3; 27.9 kDa), V4 (pI 6.5; 26.1 kDa), V5 (pI 6.8; 25.9 kDa), and V6 (pI 6.7; 25.9 kDa). Compared to controls, except for variants V2-V6 in PRL-adenomas, V2 in FSH+-adenomas, and V3 in NF--adenomas, the other PRL variants were significantly downregulated in each subtype of pituitary adenomas. Moreover, the pattern of those six PRL variants was significantly different among five subtypes of pituitary adenomas relative to control pituitaries. Different hPRL variants might be involved in different types of PRL receptor-signaling pathways in a given condition. Those findings clearly revealed the existence of six hPRL variants in human pituitaries, and the pattern changes of six hPRL variants among different subtypes of pituitary adenomas, which provide novel clues to further study the functions, and mechanisms of action, of hPRL in human pituitary and in PRL-related diseases, and the potential clinical value in pituitary adenomas.